Impact of public investment projects on improving the living conditions of the district of Marías population – Huánuco - Cárdenas-Ordoñez, Luz J. (2019)
The objective of the research was to determine the Impact of Public Investment projects on improving the living conditions of the population of the district of Marías - Huánuco 2007-2015. The type of research was applied, whose level of investigation was correlational. The research design was non-experimental - transversal. The research population consisted of 678 people over 18 years of age, from the district of Marías, beneficiary of the public investment projects of water and sanitation, health, education and electrification, located in the localities of Maynas, Patay Rondos, Marías, Chipaquillo, Guenehuylca, Ichic Marías, Pura, Tantacoto, Ticte, Ututo, Gorgor. The sample of the investigation was constituted by 80 people of the district of Marias, for the calculation of the size of the sample Probabilistic sampling was used. The results arrived at in the present investigation were: The public investment executed in the sanitation project, has allowed to cover in drinking water of 77.80% of the year 20007, to 100% for the year 2015, and in drainage of 96.80% to 100% for the same years, with respect to electrification coverage, has allowed a 79.90% coverage of electric power for the year 2007, endowing 100% of the population of the town of Marías for the year 2015. The conclusion: The arrival in the research was: the projects of public investment in basic sanitation improved the quality water consumption conditions of the district of Marías, since by having 100% of the population of the service they allow consuming better-quality water and more keep going.